Estrategia de ventas de Empresa Tecnicelltp ubicada en el cantón Puebloviejo, periodo 2022. - Pérez Chavalie, Tirony Vicente (2023)
The Company TECNICELLTP, is a private company that is dedicated to the repair of cell phones, sales of accessories and sales of mobile phones. Due to these circumstances, the present work is aimed at developing a SALES STRATEGY OF THE TECNICELLTP COMPANY. The objective of this case study is to analyze the strategies for the growth of sales of the Tecnicelltp company located in the Puebloviejo canton, in the period 2022. The Objectives that was reached in the present investigation allowed us to identify the strategies that are considered for the growth of sales in the company Tecnicelltp. Determine the needs of the user in the cell phone repair process for the design of the work station. Propose sales actions to increase sales by 15% in relation to the previous year the general situation of the projects that are linked to it and this is related to the line of investigation of Financial, administrative, tax, audit and control management and that At the same time, it is related to the sub-line of research Companies and public and private institutions, one of its tasks is to provide a good service to its clients. In addition, as a research method in this case study, the research method that allows obtaining information about the characteristics of the premises, employees and customers and how they are related to each other was applied. And when carrying out all these events, results were obtained about how customer service is, its promotions that the company offers, the SWOT analysis is where you could compare your threats and opportunities. In conclusion, the increase in sales helps to improve your products, good customer service to generate a purchase, implement promotions.